Zinc finger protein A20-targeting siRNA promotes pyroptosis of human rheumatoid arthritis fibroblast-like synoviocytes (Jichu yixue yu linchuang)
Objective To investigate the regulatory effect of small interfering RNA (siRNA) silencing zinc finger protein A20 on pyroptosis of rheumatoid arthritis(RA) fibroblast-like synoviocytes (HFLS-RA). Methods Human FLS-RA cell line MH7A cells were cultivated, A20 siRNA silencing group was synthesized for knocking down the human A20 gene, and then specific A20 gene siRNA and siRNA-NC(negative control)were transfected into MH7A cells using liposome method. RT-qPCR was applied to detect the expression of NLRP3 and Caspase-1 mRNA in cells.The protein expression of NLRP3 and Caspase-1 was detected by Western blot, and IL-1β and IL-18 in cell culture medium were detected by ELISA method. Transmission electron microscopy (TEM) was used to detect pyroptosis. Results After A20 knockdown, the mRNA and expression of NLRP3 and Caspase-1 in MH7A cells in the siRNA-A20 group were significantly increased as compared with the siRNA-NC group(P＜0.01). The concentration of IL-1β and IL-18 in the cell culture supernatant of the siRNA-A20 group was significantly increased compared with the siRNA-NC group (P＜0.01). Compared with the siRNA-NC group, some cells in the siRNA-A20 group showed swollen and ruptured. The integrity of the cell membrane was also lost, and a large area of edema was present in the cell. In addition, a blurred depression of the local nuclear membrane was noted, while an increase in heterochromatin pyknosis was accompanied by their uneven distribution as well as their aggregation around the nuclear membrane. Conclusions Silencing of A20 gene with siRNA might promote NLRP3/Caspase-1 mediated pyroptosis in HFLS-RA, which lays an experimental foundation for new clinical treatment methods of RA.